Functional 3D architecture in an intrinsically disordered E3 ligase domain facilitates ubiquitin transfer - Paul Murphy (Nature Portfolio, 2020)
RNF4 is a prototypical single-subunit E3 enzyme that can bind both substrate and ubiquitin-loaded E2. Here, the authors show that the RNF4 N-terminal region, although lacking a defined secondary structure, maintains a compact global conformation to facilitate ubiquitin transfer to the substrate.